Analysis of Procedures for Providing Subsidized Housing Loan (KPR) to Increase the Effectiveness of Loan Provision to Bank X - Afifah, Dien Ayu Nur; Fauji, Diah Ayu Septi (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to analyze Bank X's procedures for granting Subsidized Housing Loans (KPR), identify obstacles faced, and provide recommendations to increase the effectiveness of the credit granting process. Design/Methode/Approach: The research method used in this study is qualitative descriptive, which explains, describes, and answers questions in more detail and by the actual situation of the problem to be studied. In this study, we analyze in detail the procedure for granting Subsidized Housing Loans (KPR) at Bank X. Research Finding: The procedure for granting Subsidized Housing Loans (KPR) at Bank X has gone well, even though several obstacles remain. The procedure starts with several stages: submission by users/customers, checking the requirements and completeness of documents by Consumer Loan Sales (CLS), interviews and checking SLIK by Consumer Loan Sales (CLS), verification and assessment, credit agreements, and disbursement. Theoretical Contribution/Originality: This research contributes to the development of management theory by reinforcing that it is essential to implement standard operating procedures (SOPs) in business. Practitioner/Policy implication: The results of this study provide practical recommendations to simplify administrative procedures, adopt digital solutions to reduce manual processes, improve staff training to improve service quality so that misinformation does not occur, display procedures and requirements in detail, and provide time deadlines at each stage. This recommendation can help Bank X and similar institutions optimize the procedure for granting subsidized mortgages. Research limitation: This research is limited to one branch of Bank X, so the findings may not be generalized to other branches or institutions. To validate and expand the findings, further research can be carried out with comparative studies in several branches or banks.